2015
DOI: 10.1111/lang.12123
|View full text |Cite
|
Sign up to set email alerts
|

Phonological Development in Hearing Learners of a Sign Language: The Influence of Phonological Parameters, Sign Complexity, and Iconicity

Abstract: The present study implemented a sign-repetition task at two points in time to hearing adult learners of British Sign Language and explored how each phonological parameter, sign complexity, and iconicity affected sign production over an 11-week (22-hour) instructional period. The results show that training improves articulation accuracy and that some sign components are produced more accurately than others: Handshape was the most difficult, followed by movement, then orientation, and finally location. Iconic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(82 citation statements)
references
References 58 publications
2
75
4
1
Order By: Relevance
“…a visual, rather than auditory modality as there had been no studies on this prior to our study (since our study there have been other researchers exploring this for recreational language learners, e.g. Ortega and Morgan (2015)). Carroll (1967) identified four components of spoken language learning aptitude:…”
Section: Language Learningmentioning
confidence: 99%
“…a visual, rather than auditory modality as there had been no studies on this prior to our study (since our study there have been other researchers exploring this for recreational language learners, e.g. Ortega and Morgan (2015)). Carroll (1967) identified four components of spoken language learning aptitude:…”
Section: Language Learningmentioning
confidence: 99%
“…In the training phase, participants imitated signs immediately after observing them on the screen, so this resulted in high degree of accuracy under our coding scheme. Participants occasionally produced some of the errors that have been reported in the literature, such as inaccurate hand configuration (Ortega & Morgan, 2015) and production of the mirror image of signs (Rosen, 2004), but these renditions were still intelligible. Analysis of the renditions produced during the testing phase showed that, in general, having observed each sign five times during the experiment led to successful sign learning.…”
Section: Discussionmentioning
confidence: 99%
“…In support of the latter view, participants in our study were not instructed on whether they should rehearse any of the movements and few spontaneously chose to do so. Moreover, research on the perception and production of signs by adult signers and nonsigners typically finds that the movement parameter is the most error prone; followed by handshape and orientation; and finally location (Bochner et al, 2011;Bochner et al, 2015;Mann et al, 2010;Ortega & Morgan, 2015;. Importantly, handshape, orientation, and location are features that can be represented in static visual imagery.…”
Section: The Role Of Visuospatial Stm In Sign Learningmentioning
confidence: 99%